2002
DOI: 10.1002/hyp.350
|View full text |Cite
|
Sign up to set email alerts
|

An approach for evaluating the hydrological effects of urbanization and its application

Abstract: Abstract:This study focuses mainly on observing urban development in Taiwan's Wu-Tu watershed from the perspective of urban hydrological theory. An approach is proposed for developing a method for incorporating available meteorological data to define the degree of change in a runoff hydrograph for urbanizing basins. The mean rainfall was estimated using the Kriging method. For calibration, two methods of calculating the effective rainfall (the -index method and the non-linear-programming (NLP) method) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 25 publications
3
100
0
1
Order By: Relevance
“…The changes in extreme high-flow conditions varied from 7 % for the 1-day maximum and 2-day maximum to 4 % for the 90-day maximum flow conditions for the agricultural scenario (L1). The results are in agreement with those of Cheng and Wang (2002), Choi and Deal (2008) and Choi (2008). The timings of annual extreme flows were similar for the base scenario and the extensive agriculture scenario; however, the timings shifted from mid-July for base scenario and agriculture (L1), to beginning and mid-January for urbanization scenarios.…”
Section: Hydrologic Alterationsupporting
confidence: 87%
“…The changes in extreme high-flow conditions varied from 7 % for the 1-day maximum and 2-day maximum to 4 % for the 90-day maximum flow conditions for the agricultural scenario (L1). The results are in agreement with those of Cheng and Wang (2002), Choi and Deal (2008) and Choi (2008). The timings of annual extreme flows were similar for the base scenario and the extensive agriculture scenario; however, the timings shifted from mid-July for base scenario and agriculture (L1), to beginning and mid-January for urbanization scenarios.…”
Section: Hydrologic Alterationsupporting
confidence: 87%
“…The study is consistent with several previous studies which highlighted the significant increases in urban growth and its effect on runoff production [10,20,[37][38][39][40][41]. The hydrological processes, over a range of temporal and spatial scales, are impacted by land use changes [21,42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Urban expansion also leads to the removal of trees and vegetation, causing a decrease in evapotranspiration. The construction of roads and culverts has effects which may include reduction of infiltration, decline in the groundwater table, increased surface runoff and a reduction of base flows [5,10,11]. Built-up areas lead to an increase in impervious surfaces which in turn reduces the runoff concentration time.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g. Rose and Peters, 2001;Cheng and Wang, 2002;Du et al, 2012;Huang et al, 2008). However, several studies have found mixed effects of urban-ization on peak flows and response times, associated with a combination of imperviousness and flood mitigation measures, especially for basins where urbanization has predominantly taken place after implementation of stormwater control legislation (e.g.…”
Section: Introductionmentioning
confidence: 99%